Risk management in the new post-covid-19 normality - Zacarías Rodríguez , Remo Eusebio (2022)
The investigation Risk management in the new post-covid-19 normality, the return to professional, educational and daily activities will not be the same as before. Citizens will be concerned about their biosecurity, about the risks to which they will be exposed in physical environments and the behavior of other citizens. In this scenario, the main challenge as organizations will be to translate into concrete and practical facts. The objective was  to determine the influence of risk management in the new normality post COVID 19. Material and Method: the research work is basic, non-experimental design, of correlational-causal cross-section, the sample 107 business partners of the Chamber of Commerce of Huancayo. The management of emerging risks such as prevention, documentation and management have 37%. In the monitoring, control and risk analysis activities with 35% of application, as for the new post-covid-19 normality, there is a 39% plan for the surveillance, prevention and control of Covid-19 in the job. With 39% they have personal protection equipment against Covid-19 and protocols for care and processes at work. We found a significance level of 0.05, risk management significantly influences the new post-COVID 19 normal, which means that risk management influences up to 58.5% of the new post-COVID 19 normal.